IMPROVING THE LOCAL ECONOMY THROUGH EMPOWERING MSMES IN DIGITAL MARKETING IN DOMBO VILLAGE, DEMAK - Lasmiatun, KMT; Prasetiyawan, Andika (TOPLAMA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in stabilizing and driving national economic growth, particularly due to their contribution to employment, productivity improvement, and their ability to survive amid the dominance of large corporations. However, MSMEs still face significant challenges, especially in product marketing. One example is MSMEs in Dombo Village, Demak Regency, which face obstacles in marketing their products optimally. This study aims to improve the marketing capacity of MSME actors through the implementation of digital marketing strategies. The method used in this activity is a descriptive approach through community service activities, which consist of location surveys, MSME actor data collection, and the implementation of digital marketing workshops. The workshop was attended by 30 MSME actors and focused on the introduction and practical use of digital platforms as marketing media. The results of the activity showed that participants experienced an increase in understanding of digital marketing, as evidenced by their enthusiasm during the practical sessions and their commitment to applying digital strategies in marketing their products. The supporting factors for the success of this activity were the interest and need of MSME actors in marketing digitalization. The inhibiting factors were the short preparation time, which resulted in an incomplete data collection process for MSME actors. Overall, this activity provided tangible benefits for SMEs by equipping them with foundational knowledge of digital marketing as a relevant marketing strategy in the era of digital transformation.